Broadband ASE source for S plus C plus L bands using hafnia-bismuth based erbium co-doped fibers - Al-Azzawi, Alabbas A. (Elsevier GMBH, 2022)
A broadband amplified spontaneous emission (ASE) source is demonstrated experimentally by using hafnia-bismuth based erbium co-doped fibers (HB-EDFs) with a total length of 200-cm as an active medium. Both of parallel and series configurations are used to generate a broadband ASE source, operating at 1.5 mu m and that cover S-, C-, and L-bands. The comparison proves that the series configuration provides a relatively larger ASE bandwidth, higher output power, higher efficiency, and lower complexity. At the optimum total pumping power of 280 mW, a broadband ASE source of 57 nm with a power ripple of +/- 7.5 dB is achieved. Besides, a total ASE power of 20.8 mW is obtained, which is equivalent to 7% of the pumping efficiency.